Nintedanib plus docetaxel as second-line therapy in patients with non-small-cell lung cancer of adenocarcinoma histology: a network meta-analysis vs new therapeutic options. (June 2017) - Popat, Sanjay; Mellemgaard, Anders; Reck, Martin; Hastedt, Claudia; Griebsch, Ingolf
Patients & methods: We provide an update to a network meta-analysis evaluating the relative efficacy of nintedanib + docetaxel versus other second-line agents in adenocarcinoma histology non-small-cell lung cancer.Results: Overall similarity of nintedanib + docetaxel versus ramucirumab + docetaxel, and versus nivolumab. Comparing nintedanib + docetaxel with nivolumab, hazards ratio (HR) of overall survival and progression-free survival (PFS) pointed in opposite directions (overall survival: HR: 1.20 [95% credible interval: 0.92–1.58]; PFS: HR: 0.91 [0.68–1.21]). Exploratory subgroup analysis indicated superiority of nivolumab in high PD-L1 expression level subgroups; results were more favorable for nintedanib in all subgroups with low (<1%, <5%, <10%) PD-L1 expression levels – in particular, with regard to PFS.Conclusion: Results demonstrated similar efficacy of nintedanib + docetaxel compared with the new therapeutic options ramucirumab + docetaxel and nivolumab, with potential differences in subgroups according to PD-L1 expression level.